Longitudinal Evaluation of Clinical and Colonization Methicillin-Resistant Staphylococcus aureus Isolates Among Veterans. (5th February 2015) - Stenehjem, Edward; Crispell, Emily K.; Rimland, David; Farley, Monica M.; Satola, Sarah W.
<x content-type="archive" xml:space="preserve">Abstract</x> Using the Veterans' Health Administration MRSA Directive as a platform to collect methicillin-resistant Staphylococcus aureus (MRSA) colonization isolates and an active MRSA infection surveillance program, the genetic relatedness of colonization and infection isolates was evaluated. Infection and colonization strain concordance was found in 85.7% of patients. The USA 500 MRSA strain was identified in 31.8% of patients. Infect Control Hosp Epidemiol 2015;00(0): 1–3